Glacial melt disturbance shifts community metabolism of an Antarctic seafloor ecosystem from net autotrophy to heterotrophy - Braeckman, Ulrike (2021)
Climate change-induced glacial melt affects benthic ecosystems along the West Antarctic Peninsula, but current understanding of the effects on benthic primary production and respiration is limited. Here we demonstrate with a series of in situ community metabolism measurements that climate-related glacial melt disturbance shifts benthic communities from net autotrophy to heterotrophy. With little glacial melt disturbance (during cold El Niño spring 2015), clear waters enabled high benthic microalgal production, resulting in net autotrophic benthic communities. In contrast, water column turbidity caused by increased glacial melt run-off (summer 2015 and warm La Niña spring 2016) limited benthic microalgal production and turned the benthic communities net heterotrophic. Ongoing accelerations in glacial melt and run-off may steer shallow Antarctic seafloor ecosystems towards net heterotrophy, altering the metabolic balance of benthic communities and potentially impacting the carbon balance and food webs at the Antarctic seafloor.